2005
DOI: 10.1016/j.jacc.2005.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Triple Versus Dual Antiplatelet Therapy After Coronary Stenting

Abstract: Compared with the dual antiplatelet regimen, triple antiplatelet therapy seemed to be more effective in preventing thrombotic complications after stenting without an increased risk of side effects. Triple antiplatelet therapy might be safely applied in patients or lesions with a high risk of stent thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 189 publications
(144 citation statements)
references
References 17 publications
8
135
0
1
Order By: Relevance
“…12 Triple therapy with aspirin and a thienopyridine (clopidogrel or ticlopidine) plus clilostrazol, a phosphodiesterase III inhibitor, has been reported to lower rates of stent thrombosis as compared to aspirin and thienopyridine alone (0.3% vs. 0.8%, respectively, OR 0.12). 13 In this report, we present a patient with acute stent thrombosis involving two different arteries in the setting of a recent ischemic stroke. The concurrence of multiple thrombo-embolic events led us to speculate that the patient may have systemically heightened platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…12 Triple therapy with aspirin and a thienopyridine (clopidogrel or ticlopidine) plus clilostrazol, a phosphodiesterase III inhibitor, has been reported to lower rates of stent thrombosis as compared to aspirin and thienopyridine alone (0.3% vs. 0.8%, respectively, OR 0.12). 13 In this report, we present a patient with acute stent thrombosis involving two different arteries in the setting of a recent ischemic stroke. The concurrence of multiple thrombo-embolic events led us to speculate that the patient may have systemically heightened platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence was also within the same range (0-2.0%) as in previous reports that included elective BMS and SES implantations. [10][11][12] In addition, there was no new onset of late stent thrombosis in either group between 30 and 300 days after primary PCI. In a recent pooled analysis including 10 randomized studies, Moreno,et al 12) demonstrated that drug-eluting stents did not increase the risk of stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…This combination has been shown to be both effective and safe, with particular benefits noted in patients with diabetes. 2,32 However, the use of 3 antiplatelet agents has not been described in the neurointerventional literature. In addition to modifications to the traditional aspirin and P2Y12 inhibitor combination, single-drug therapies such as the GP-IIb/IIIa inhibitors abciximab and tirofiban have been described.…”
Section: Pharmacology Of Antiplatelet Medicationsmentioning
confidence: 99%